Atopic diseases and airway-related symptoms in Bavarian pre-schoolers: determinants and association with immunization. (26th August 2021) - Korbely, Christine; Weinberger, Alisa; Kutzora, Susanne; Huß, Jonas; Hendrowarsito, Lana; Nennstiel, Uta; Heißenhuber, Annette; Herr, Caroline; Heinze, Stefanie; ,
Abstract: Background: Atopic diseases are among the most common chronic conditions in childhood. Causes of allergies are manifold. The aim of this paper is to evaluate risk factors for atopic diseases and unremitting wheeze and to examine if there is an association between measles, mumps and rubella (MMR) vaccination and atopic dermatitis, asthma and unremitting wheeze in Bavarian pre-schoolers. Methods: Parents filled out a questionnaire on children's health and environmental and socioeconomic factors. The questionnaire was administered within the Health Monitoring Units in a cross-sectional study in Bavaria, Germany (2014/2015). Data on vaccinations were obtained via the School Entrance Examination, a mandatory examination for pre-school children in Bavaria. Rates of influential factors of atopic diseases and wheeze, MMR and DTP (diphtheria, pertussis and tetanus) vaccination were calculated for all children stratified by health outcomes. To examine if there is an association between MMR vaccination and health outcomes, a multiple logistic regression analysis was performed. Results: Data were available for 3237 individuals. Symptoms and diseases were more frequent in boys. Higher parental education was associated with a higher prevalence of atopic dermatitis. There were no significant associations between any of the health outcome groups and MMR vaccination in the multiple logistic regression models with adjustment for potential confounders. Conclusions: The present study is in line with the current state of research that MMR vaccination is not associated with atopic diseases.